Outcomes of microincision vitrectomy surgery with internal limiting membrane peeling for macular edema secondary to branch retinal vein occlusion - Sato S (Dove Medical Press, 2015)
Shimpei Sato,1 Maiko Inoue,2 Shin Yamane,2 Akira Arakawa,2 Mikiro Mori,1 Kazuaki Kadonosono2 1Department of Opthalmology, Toranomon Hospital, Tokyo, Japan; 2Department of Ophthalmology, Yokohama City University Medical Center, Yokohama, Japan Purpose: To evaluate the anatomic and functional effect of microincision vitrectomy surgery (MIVS) with internal limiting membrane (ILM) peeling for macular edema secondary to branch retinal vein occlusion (BRVO).Methods: The medical records of 101 eyes of 101 patients who had undergone MIVS with ILM peeling for macular edema secondary to BRVO were studied. Patients were classified into ischemic and non-ischemic BRVO based on angiograph. The best-corrected visual acuity (BCVA) and central foveal thickness (CFT), determined by spectral domain optical coherence tomography, were evaluated at baseline and at 1, 3, 6, and 12 months postoperatively.Results: Preoperative mean logarithm of the minimum angle of resolution (logMAR) BCVA ± standard deviation (SD) was 0.52±0.43 and mean CFT ± SD was 489.4±224.9 µm. Postoperative mean BCVA ± SD values were 0.41±0.35, 0.35±0.41, 0.29±0.36, and 0.25±0.41, and mean CFT values were 370.1±148.9, 327.5±157.5, 310.9±154.9, and 274.4±135.3 µm at 1, 3, 6, 12 months, respectively. The mean BCVA was significantly improved at 3, 6, and 12 months postoperatively (all P<0.05), and the mean CFT was significantly decreased at all postoperative follow-up time points (all P<0.05). At the 12-month postoperative evaluation, BCVA had improved by 0.2 logMAR units in 50 eyes (60.0%) with ischemic BRVO and in nine eyes (50.0%) with non-ischemic BRVO. Six eyes (6.0%) experienced recurrence or persistence of macular edema at 12 months postoperatively.Conclusion: MIVS with ILM peeling for macular edema secondary to BRVO is effective in improving visual acuity and foveal morphology with low recurrence of macular edema. Keywords: MIVS, ILM, BRVO, central foveal thickness, CFT